Sports experience, affects and life satisfaction in Portuguese athletes with disabilities - Miguel Jacinto; Nuno Couto; Anabela Vitorino; Teresa Bento; Rui Matos; Diogo Monteiro; Nuno Amaro; Raul Antunes; Luís Cid (BMC Psychology)
Abstract This study aims to validate the Portuguese version of the Satisfaction with Life Scale (Cronbach’s alpha = 0.82) and the Positive and Negative Affect Scale (Cronbach’s alpha = 0.86 for positive affect and 0.89 for negative affect) for people with disabilities and to examine the association between engaging in physical activity and affective responses, investigating the relationship with satisfaction with life. 143 Portuguese with disabilities filled in the Portuguese version of the scales. The findings endorsed the single factorial structure and reliability of the Satisfaction with Life Scale [χ2/df = 6.3, B-S p = 0.487, TLI = 0.989, CFI = 0.995, SRMR = 0.0263, RMSEA = 0.043 (CI = 0, 0.130)]. For Positive and Negative Affect Scale, the results also confirmed the factorial structure and reliability [χ2/df = 1.871, B-S p = 0.114, TLI = 0.891, CFI = 0.918, SRMR = 0.0778, RMSEA = 0.078 (CI = 0.048, 0.108)]. On the other hand, the structural model presented satisfactory fit to the data [χ2/df = 1.436, B-S p = 0.269, TLI = 0.917, CFI = 0.930, SRMR = 0.0748, RMSEA = 0.055 (CI = 0.033, 0.075)]. Significant direct effects have been found, as has been theoretically proposed, namely: years of practice displayed a positive and significant association with positive affect; positive affect was positively associated with satisfaction with life (β = 0.073, CI = 0.020, 0.139; p = 0.031).